One-Pot Oxidative Conversion of Alcohols into Nitriles by Using a TEMPO/PhI(OAc)2/NH4OAc System - Vatèle, Jean-Michel (Synlett, 2014)
A direct conversion of alcohols into nitriles with 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO), iodosobenzene diacetate, and ammonium acetate as a nitrogen source is reported. This transformation, which proceeds through an oxidation–imination–aldimine oxidation sequence in situ, has been applied to a range of aliphatic, benzylic, heteroaromatic, allylic, and propargyl alcohols. Highly chemoselective ammoxidation of primary alcohols in the presence of secondary alcohols was also achieved.
Keywords: alcohols; chemoselectivity; nitriles; oxidation; TEMPO